2017
DOI: 10.7575/aiac.alls.v.8n.6p.100
|View full text |Cite
|
Sign up to set email alerts
|

Improving English Speaking Fluency: The Role of Six Factors

Abstract: This qualitative study, using an open interview, set out to investigate the roles six factors, including age, university education, teachers of English Language institutes, teaching English, dictionary, and note-taking, played in improving English speaking fluency of seventeen fluent Iranian EFL speakers. The participants were chosen purposefully based on the speaking scale of Common European Framework of Reference for Languages (CEFRL). The findings indicated that early age had a great impact on the participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 5 publications
0
14
0
1
Order By: Relevance
“…Consequently, other studies determined that students stated that they did not have enough opportunities to speak English within or outside of class and when they were given the opportunity to communicate and exchange information in English, in written or spoken form, they showed great difficulty. in doing so, which caused negative reactions in their motivation to learn the language (Chamba et al, 2019;Shahini & Shahamirian, 2017). For this reason, teacher support, student autonomy, effort to learn new vocabulary and motivation are the main factors that are needed in learning a language.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, other studies determined that students stated that they did not have enough opportunities to speak English within or outside of class and when they were given the opportunity to communicate and exchange information in English, in written or spoken form, they showed great difficulty. in doing so, which caused negative reactions in their motivation to learn the language (Chamba et al, 2019;Shahini & Shahamirian, 2017). For this reason, teacher support, student autonomy, effort to learn new vocabulary and motivation are the main factors that are needed in learning a language.…”
Section: Resultsmentioning
confidence: 99%
“…Along with the other researches, fluency plays a crucial role in achieving the purpose of communication in conversation [2]. The previous research findings showed that the classroom becomes the main place and source where the students can practice their English-speaking fluency in the EFL context.…”
Section: Introductionmentioning
confidence: 94%
“…There were nine factors affecting English speaking fluency, namely linguistic factors, psycholinguistics factors, age, sociolinguistic factors, bilingualism, individual differences or personality, developmental factors, the frequency of the input, and exposure [2][3] [4]. Along with the demand for rapid technology development in industrial revolution 4.0, research also emphasized research on the importance of developing students' speaking skills in the classroom [1].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, other studies determined that students stated that they did not have enough opportunities to speak English within or outside of class and when they were given the opportunity to communicate and exchange information in English, in written or spoken form, they showed great difficulty. in doing so, which caused negative reactions in their motivation to learn the language (Chamba et al, 2019;Shahini & Shahamirian, 2017). For this reason, teacher support, student.…”
Section: Specific Needs Of Teaching and Learning Englishmentioning
confidence: 99%